Phase formation, microstructural and superconducting properties of YBCO added Ca-compounds extraction eggshells - Yap, Siew Hong; Awang Kechik, Mohd Mustafa; Humaidi, Syahrul; Mohd Shariff, Khairul Khaizi; Baqiah, Hussien; Chen, Soo Kien; Lim, Kean Pah; Mohd Zaid, Mohd Hafiz; Yaakob, Yazid; Abdul Karim, Mohd Khalis; Talib, Zainal Abidin; Loh, Zhi Wei; et al. (Elsevier B.V., 2025)
For several decades now, the emergence and production of high-quality bulk rare-earth-based superconductors, particularly YBa2Cu3O7-δ (YBCO/Y-123), have been noteworthy advancements with potential implications in various fields. This unique research investigated the potential of using chicken eggshells as a source of calcium compounds (CaO, CaCO3 and Ca(OH)2) for the synthesis of YBCO. The green approach synthesis of YBCO added with Ca-compounds (0.0100 wt% ≤ x ≤ 0.6000 wt%) was conducted in a systematic manner via thermal treatment method. The crystal structure, surface morphology, and chemical composition of the specimens were characterized by X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM), and Energy Dispersive X-Ray Spectroscopy (EDX). The results showed the formation of orthorhombic Y-123 phase, Pmmm space group with the high-intensity peaks of Y-123. The addition of Ca-compounds proposed a different trend of grain degradations in the YBCO matrix system with the appearance of Ca-compounds' impurity phases. The superconducting properties such as electrical resistivity analyzed using electrical resistance measurement. Surprisingly, the superconducting parameters improved after Ca-compounds were added into the YBCO system. The hole concentration, p reached the highest value among all the specimens with the lowest superconducting transition width, ∼ΔTc = 3.805 K (Tc-onset = 93.223 K and Tc(R = 0) = 89.418 K) for the lowest concentration of Ca-compounds i.e., 0.0375 wt%. This great finding targeted the green approach impurity materials into YBCO system that can usefully enhance the superconducting properties at high temperature which covers the idea of addition with deficient concentration Ca-compounds.